Accomplishing Education in Open Universities through the Agency of Digital Media. Issue 2 (1st December 2015) - Saludadez, Jean A.
Abstract : This paper attempts to explain why and how open universities accomplish their educational purposes. The research explores the use of the Agency Framework as a theoretical anchor for examining and explaining how education/learning is possible at a distance. The paper illustrates how digital media are agents that participate in the accomplishment of teaching and learning research online. The study employs the ventriloqual approach that involves a three-step process of: (1) collecting archived/recorded online interactions; (2) identifying markers through which digital media appear to recurrently and iteratively express themselves in the recorded interactions; and (3) understanding or hearing what the markers are made to say. Using this approach, the paper shows how digital media afford the creation of interactive activities in a graduate level research course in an open university, enabling students to go through designing and implementing research using both quantitative and qualitative methodologies. Surfacingthe agentive roles of digital media stagedat teacher-students interactions provides insights into why education can be accomplished at a distance.